Mechanical and dissolution properties of Eudragit L100 and S100 films in buffer solutions - Ambudkar, Vaibhav Jindas; Chauhan, Rashmi (Creative Pharma Assent, 2025)
Background: Methacrylic acid (MAA) and methyl methacrylate (MMA) affect the mechanical and dissolution properties of enteric polymers, such as Eudragit L100 and S100. Their composition determines polymer flexibility, strength, and solubility, which are critical for pharmaceutical enteric coatings. This study examines the impact of the MAA: MMA ratio on the mechanical and dissolution properties of Eudragit L100 (1:1) and Eudragit S100 (1:2) films. Methodology: Mechanical testing assessed stiffness, tensile strength, and flexibility. Dissolution studies evaluated solubility at different pH levels, measuring peak dissolution rates. Results and Discussion: Eudragit L100, with more MAA, was stiffer and more brittle, while Eudragit S100 had higher tensile strength but reduced flexibility. Acidic conditions weakened both, due to water interactions with MAA. Eudragit L100 dissolved rapidly at pH 7.2 (90% mass loss in 60 min, peak 30.4 mg/g·min at 10 min), whereas Eudragit S100 showed minimal dissolution at lower pH, but dissolved significantly at pH 8.0 (64.5% at 180 min, peak 6.7 mg/g·min at 30 min). Larger dissolution volumes, maintained concentration gradients, enhancing dissolution, while high-capacity buffers stabilized pH and improved solubility. Conclusion: MAA: MMA composition critically affects the mechanical and dissolution properties of Eudragit L100 and S100, with concentration gradients playing a key role in dissolution, informing their application in enteric coatings.